2007
DOI: 10.2478/s11756-007-0050-3
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of fungi associated with wheat and barley seedling emergence and fungicide efficacy of seed treatment

Abstract: Presented study focused on the influence of Cochliobolus sativus isolates origin on pathogenicity towards wheat and barley seedlings in comparison with pathogenicity of certain Fusarium species and Microdochium nivale. The efficacy of fungicide seed treatment against C. sativus was estimated. The C. sativus isolates were collected from different locations and were isolated from wheat, barley and sunflower seeds. The pathogenicity of C. sativus, Fusarium species and M. nivale towards germinating seedlings were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
(17 reference statements)
0
6
0
1
Order By: Relevance
“…M. nivale was more common on winter barley than on winter wheat (Dawson, Bateman, 2001). In another study winter wheat was more susceptible to Fusarium species and M. nivale than winter barley (Hudec, 2007). Usually Microdochium species is present as one or both (Nicholson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…M. nivale was more common on winter barley than on winter wheat (Dawson, Bateman, 2001). In another study winter wheat was more susceptible to Fusarium species and M. nivale than winter barley (Hudec, 2007). Usually Microdochium species is present as one or both (Nicholson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the south region of Brazil, barley seeds are generally commercialized after chemical treatment. However, most of these chemical treatments have not eradicated A. alternata, B. sorokiniana and D. teres (12,13,23). In the present study, barley seeds were demonstrated to present a viable inoculum of A. alternata, B. sorokiniana and D. teres during storage, since incidence and viability of these fungi were maintained in the seeds.…”
Section: Resultsmentioning
confidence: 54%
“…Nevertheless, seed health testing has revealed that a large number of treated seeds are infected by A. alternata, B. sorokiniana and D. teres (4). Moreover, incidence of seed-borne fungi in harvested seeds is high, further compromising the treatment effectiveness (6, 13,23). Incorrect or inefficient fungicide treatment may allow the survival of necrotrophic fungi and the spread of diseases to other uninfested sites (6, 7).…”
mentioning
confidence: 99%
“…Generally it is accepted that F. graminearum is more resistant to fungicides than F. poae. Using several fungicides such as diphenoconazole, tebuconazole, iprodione,… it was demonstrated that the sensitivity of F. graminearum was lower compared to F. poae (Hudec, 2007;Mullenborn et al 2008). Till now, we have no clear explanation for this discrepancy, however, possibly the isolate, the incubation temperature, the culture conditions might influence the sensitivity response in both species.…”
Section: Fig 2 Effect Of a Dilution Series Of Fluoxastrobin+prothiomentioning
confidence: 68%